Multiple footprint indicator assessment: implications on consumer preferences and welfare - Owusu-Sekyere, Enough (University of the Free State, 2017)
Assessments of multiple environmental footprint sustainability indicators, such as water and carbon footprints, are regarded as cornerstones in achieving the world’s sustainability goals and the reduction of the freshwater scarcity risk. Water and carbon footprint assessments are gaining much prominence because about four billion people face severe water scarcity across the globe amidst climate changes and population growth. Attaining environmental sustainability in terms of carbon emissions and water use, as well as economically efficient water use, requires detailed and thorough assessment that is not limited to a single indicator. The prevailing environmental impacts relating to water scarcity and carbon emissions in South Africa require in-depth and comprehensive information on water and carbon footprints to effectively guide South African policy and decision makers in formulating appropriate policies to guide freshwater use and reduce greenhouse gas (GHG) emissions. Hence, the main objective of this research was to conduct a multiple footprint indicator assessment of the dairy industry, with particular emphasis on the water and carbon footprints of milk produced and processed in South Africa. Additionally, the study assessed the impact of carbon and water footprint sustainability attributes on consumers’ behaviour and welfare in South Africa. The economic productivity of water utilisation along the dairy value chain was also explored. The Water Footprint Network assessment methodology was employed to examine the water footprint and economic water productivities of dairy products in South Africa for the periods 1996–2005 and 2006–2013. The findings reveal that the total water footprints of the selected dairy products considered in this study are higher than the global averages. During the latter period (1996 to 2005), South African dairy producers utilised more green water in their dairy production. Products such as butter and cheese, whether grated or not grated, powdered or not powdered, and blue-veined and cheese of all kinds, had the highest total water footprints among all the dairy products in South Africa. In terms of production system, the study reveals that dairy production under a sole grazing (mainly pasture-fed) system has high water footprints and low economic water productivities, relative to mixed production systems, for the period 2006–2013. Therefore, given that blue water is becoming scarcer in South Africa, it is imperative for dairy livestock producers to shift their production to a system that is economically productive and has low water footprints. The water footprints of most of the dairy products for period 2006–2013 have reduced by varying amounts, relative to 1996–2005, which shows that water users along the dairy industry chains are managing water cautiously. The research findings have shown that dairy products have high economic water productivities, and suggest that profit maximising and environmentally sustainable dairy producers and water users should integrate both blue water sustainability and economic water productivity indicators in their production decisions. Regarding economic water productivity assessments along the dairy value chain in South Africa, the findings from this research reveal that the value added to milk and water as it moves along the value chain varies from stage to stage, with the highest value being attained at the processing level, followed by the retail and farm gate levels, respectively. The conclusion drawn from this finding is that milk production in South Africa is economically efficient in terms of water use. However, water utilisation for feed production accounts for about 98 % of the total water footprint of milk with 3.3% protein and 4% fat. Despite the high proportion of water used in feed production, the study suggests that feed production is economically efficient in terms of cost and water use. It is worth concluding that not all economically water productive feed products are significant contributors to milk yield. Therefore, it is important for future ecological footprint assessments to take into account the value added to output products and economic water productivities along the product’s value chain, rather than relying only on water footprint estimates. The Life Cycle Assessment approach was applied to examine the carbon footprint of milk, as well as the parameters that account for the largest impact on the carbon footprint of milk produced under the total mixed ration (TMR) feeding system in South Africa. The total carbon footprint of milk with 4% fat and 3.3% protein produced and processed in South Africa was 2.72 kg CO2e per kg. Specifically, methane accounted for 58% of the total carbon footprint, followed by nitrous oxide (31.6%) and carbon dioxide (10.5%), respectively. About 99% of the methane emissions emanated from enteric fermentation. More than half of the direct nitrous oxide emitted came from excreta and manure management. Fertiliser production and application alone accounted for about 78% of the total carbon dioxide emitted along the milk product chain. Findings from a sensitivity analysis revealed that, by reasonably changing one emission parameter, holding all the others constant, the total carbon footprint could increase considerably by about 17%. The study further highlights the point that the key parameters that need much attention in the estimation of GHG emissions are the methane emission factor for enteric fermentation and the emission factor for direct nitrous oxide emission, as well as dry matter intake. The main conclusion from these findings is that in order to attain more accurate and consistent carbon footprint estimates at national and regional levels, it is imperative to expand our knowledge on key practices, activities and parameters that affect key contributors to carbon footprints. This suggests the establishment of country- and regional-specific emission factors to be used as benchmarks for calculating carbon footprints at local and regional levels, and across industries. The discrete choice experiment and latent class modelling technique were employed to examine consumers’ stated preferences for water and carbon footprint-labelled food products from the viewpoint of low- and high-income South African consumers. It was interesting to find that there are varying consumers’ preference attitudes towards environmentally sustainable attributes between low- and high-income classes. Thus, there are profoundly heterogeneous consumer segments within low- and high-income classes. This heterogeneity in preferences within both sub-samples is better explained at the segment level, rather than at the individual level. The study reveals that there are more distinct consumer segments among low-income consumers, relative to high-income consumers. It was found that the low-income class consisted of water sustainability advocates, carbon reduction advocates, keen environmentalists, and environmental neutrals. The high-income class, on the other hand, comprises keen environmentalists, environmental cynics, and environmental neutrals. The conclusion drawn from these findings is that the inherent significant variations in preferences for environmentally sustainable attributes across segments and income groups opens room for the formulation of feasible and segment-specific environmental sustainability policies and marketing strategies aimed at changing consumers’ attitudes towards environmentally sustainable products. The study suggests the demographic targeting of consumer segments, sustainability awareness, and segment-specific educational campaigns designed to enhance subjective and objective knowledge of environmental sustainability as policy options that can be adopted to promote environmental sustainability and marketing of environmentally sustainable food products. In terms of welfare implications, the study adopted the compensating surplus welfare estimation approach and ascertained that the welfare effects arising from water and carbon footprint sustainability policies will have varying effects on different consumer classes. This suggests that there are pertinent segmental equity issues that need to be addressed when designing environmental sustainability policies in South Africa. Future studies on preferences for environmentally sustainable products should not be limited to willingness to pay estimates only; rather, compensating surplus estimates should also be computed for efficient and effective policy guidance. A conceptual framework is provided, which depicts relevant factors to be considered in order to fully understand consumers’ preferences and choice of environmentally sustainable products in South Africa. Additionally, this research has provided a framework for environmental footprint labelling and methods for estimating and conveying footprint information on food products in South Africa. Generally, this research concludes that it is expedient to achieve an integration of multiple footprints indicator assessments that establish harmonisation and benchmarks for sustainable and economically efficient water use and GHG emission reduction in arid and semi-arid regions such as South Africa. Water and carbon footprint assessments comprise an expedient tool for evaluating the possible impact of food production and products on water resources and climate change.
Thesis (Ph.D. (Agricultural Economics))--University of the Free State, 2017
Keywords: Environmental footprints; Water footprint network; Footprint indicator